Case report: A case of epidermolysis bullosa complicated with pyloric atresia and a literature review - Luo, Caiyun; Yang, Liucheng; Huang, Zhaorong; Su, Yuqian; Lu, Yi; Yu, Daiyue; Zhang, Mengzhen; Wu, Kai (Frontiers in Pediatrics, 2023)
Objective: This article aims to explore the diagnosis, molecular characteristics, treatment, and prognosis of epidermolysis bullosa with pyloric atresia (EB-PA). Methods: The clinical manifestations, diagnosis and treatment, and genetic characteristics of a patient with EB-PA admitted to our hospital were analysed. The disease subtypes, concomitant abnormalities, molecular characteristics, and prognosis of patients with EB-PA were summarized by searching the EB-PA-related literature since 2011. Results: We present a very low birth weight female infant with skin blisters and pyloric obstruction. Exome sequencing revealed heterozygous mutations in the ITGB4 gene: c.794dupC (p. S265fs*5) and c.2962G>A (p.A988T). This infant was diagnosed with EB-PA. Coverage of the wounds and Penicillin were used to prevent infection, but the patient eventually developed severe sepsis. A literature review was carried out including 49 cases of EB-PA; among these cases, 34 were preterm infants, weighing between 930 and 3640 g. Of these EB-PA patients, 28 had accompanying malformations, including urinary system malformations and aplasia cutis congenita (ACC). Thirty-two patients identified the subtype of EB-PA, of whom 25 were diagnosed with junctional epidermolysis bullosa (JEB), 6 with epidermolysis bullosa simplex (EBS), and 1 with dystrophic epidermolysis bullosa (DEB). Genetic testing was conducted on 23 patients, of whom 15 carried Integrin Beta-4 (ITGB4) gene mutations and one JEB patient carried an Integrin Alpha-6 (ITGA6) gene mutation; 4 of the 5 EBS patients had Plectin (PLEC) gene mutations, and the other had an ITGB4 mutation. ITGB4 mutation cases involved 29 mutation sites, primarily concentrated in the region encoding the integrin beta subunit; PLEC mutation cases involved 7 mutation sites. Among all cases, 43 underwent pyloric atresia surgery, of whom 24 died postoperatively, and 6 without surgery therapy died within a short period. Conclusion: EB-PA is a rare genetic disorder characterized by increased skin fragility and PA involving mutations in the ITGB4, PLEC, or ITGA6 genes. EB-PA has a high incidence of complications and mortality, surgery and supportive therapy are currently the most common treatment options.